2008
DOI: 10.1021/jp077088o
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Property and Photostability of J-Aggregate Thin Films of Thiacyanine Dyes Prepared by the Spin-Coating Method

Abstract: By use of electrostatic interactions of dye molecules and poly(diallyldimethylammonium chloride) (PDDA), the spin-coating technique has been successfully applied to the preparation of stable J-aggregate thin films of thiacarbocyanine dyes on a polycarbonate or quartz plate. The J-aggregate thin films were prepared by the spin-coating of PDDA aqueous solution on dye thin films prepared on a substrate by the spin-coating of 2,2,3,3-tetrafluoro-1-propanol solution of dyes. Photophysical properties of the dye thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 45 publications
2
33
0
3
Order By: Relevance
“…The formation of thin films on their surface can be achieved by exploring the principle of layer-by-layer assembly [147,148]. Thus the films of PIC dye on a cellulose acetate support were prepared by spin coating [149], and it was reported that the spin-coating of dye-polymer mixtures allows obtaining stable thin layers of J-aggregates [150].…”
Section: J-aggregates Formed On Scaffoldsmentioning
confidence: 99%
“…The formation of thin films on their surface can be achieved by exploring the principle of layer-by-layer assembly [147,148]. Thus the films of PIC dye on a cellulose acetate support were prepared by spin coating [149], and it was reported that the spin-coating of dye-polymer mixtures allows obtaining stable thin layers of J-aggregates [150].…”
Section: J-aggregates Formed On Scaffoldsmentioning
confidence: 99%
“…The J-band is attributed to delocalized Frenkel-type exciton states present in the assemblies of dye molecules interacting by electrostatic forces when J-aggregate is formed in concentrated solution or thin films [21]. Photophysical properties of the film of cyanine have been investigated by determining the fluorescence quantum yields and lifetimes [22][23][24]. A novel hybrid organic/inorganic nanocomposite of alternating monolayers of J-aggregated cyanine and crystalline semiconductor quantum dots have been fabricated by a layer-by-layer self-assembly technique [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus ultrasound may induce disaggregation of weakly connected aggregate. Generally, the aggregation of organic dyes induces enhancement of internal conversion, 11,12 and the aggregate shows lower Ί Š than monomer according to eq 1,where Ί isc is the quantum yield of intersystem crossing, k isc , k f , and k ic are rate constants of intersystem crossing, fluorescence, and internal conversion, respectively. On the basis of this fact, we expected that the OFF to ON switching of singlet oxygen sensitization can be achieved by using disaggregation of photosensitizer induced by sonication.…”
mentioning
confidence: 99%
“…Thus ultrasound may induce disaggregation of weakly connected aggregate. Generally, the aggregation of organic dyes induces enhancement of internal conversion, 11,12 and the aggregate shows lower Ί Š than monomer according to eq 1,…”
mentioning
confidence: 99%